CONTRIBUTION OF LAMPUNG COFFEE COMMODITY TO THE ECONOMIC IMPROVEMENT OF LAMPUNG PROVINCE - Wendy Aprianto; Usep Syaipudin; Muslimin (Pustaka Peradaban, 2022)
This research aims to find out the competitiveness of Lampung coffee export commodities against other export products in Lampung province as well as the role of Lampung coffee export commodities to regional development seen from economic growth (PDRB) of Lampung Province. Free variables in this study include Exports, Investments and Taxes, while the bound variables in this study are PDRB Lampung. The research data was obtained from the Plantation Office (Disbun) Prov Lampung and BPS Lampung. The analysis tool used is Vector Error Correction Models (VECM). In this study also used the calculation of RCA and EPD indices to analyze the performance of Indonesian coffee exports. Based on calculations using E-Views obtained that Investment and Taxes have a significant effect on the PDRB. In addition, the significant influence of Lampung coffee exports on Investment and Taxes shows that Coffee is a regional strategic export commodity and contributes revenue to the region. The results of VECM testing show that in the long run variables will affect each other. That Lampung coffee commodities have an effect in the long term on regional economic growth and are able to boost regional investment and income.